Assessing the Adjustment Implications of Trade Policy Changes Using TRIST : Tariff Reform Impact Simulation Tool - Brenton, Paul; Saborowski, Christian; Staritz, Cornelia; von Uexkull, Erik (2012)
TRIST is a simple, easy to use tool to assess the adjustment implications of trade reform. It improves on existing tools. First, it is an improvement in terms of accuracy because projections are based on revenues actually collected at the tariff line level rather than simply applying statutory rates. Second, it is transparent and open; runs in Excel, with formulas and calculation steps visible to the user; and is open-source and users are free to change, extend, or improve according to their needs. Third, TRIST has greater policy relevance because it projects the impact of tariff reform on total fiscal revenue (including VAT and excise) and results are broken down to the product level so that sensitive products or sectors can be identified. And fourth, the tool is flexible and can incorporate tariff liberalization scenarios involving any group of trading partners and any schedules of products. This paper describes the TRIST tool and provides a range of examples that demonstrate the insights that the tool can provide to policy makers on the adjustment impacts of reducing tariffs.